Kajian Pengentasan Desa Tertinggal Melalui Pendekatan Indeks Desa Membangun - Panji Hendrarso; Pryo Handoko; Miftah Faiz Ali Ramdhani; Nopi Andayani; Reni Tania (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This research is motivated by the phenomenon of the number of underdeveloped villages in Keroncong District, even though the area is in the capital city of Pandeglang, not in an area far from the center of the capital city. As it is known that: Regulation of the Minister of Villages for Development of Disadvantaged Regions & Transmigration (Permendesia PDT Trans) Number 2 of 2016 concerning the Developing Village Index (IDM) classifies Village Status into 5 (five) Village statuses. Banten Province has 4 regencies which oversee the village administration. Of the four regencies, Pandeglang Regency has the most underdeveloped villages. Meanwhile, the closest sub-district to the Pandeglang Regency government and the most underdeveloped village is Keroncong District. The purpose of this study is to reveal the cause of the number of underdeveloped villages even though the area is in the center of the capital city. The locus of this research is all villages in Keroncong District. The data used is secondary data, namely from the Department of Community Empowerment of Pandeglang Regency and Banten Province and the Central Statistics Agency (BPS) of Pandeglang Regency, BPS of Banten Province. The analytical technique used in this research is descriptive qualitative analysis and content analysis. The results showed that the development of village status in Keroncong District was dominantly included in the category of underdeveloped villages. There are two villages that fall into the category of not being left behind, with the category of developing. The two villages are Bangkonol village and Pasir Karag village. Bangkonol Village has a developing status because of the easy access to the national road that crosses the Pandeglang and Lebak Regencies and has close access to the Pandeglang Regency government center. Meanwhile, Pasir Karag Village has the status of a Developing Village because of its location close to the government center of the Keroncong sub-district, the number of government public facilitiesand a high community work ethic in entrepreneurship.